Fibrous cellulose composite resin, fibrous cellulose-containing material, and method for producing fibrous cellulose composite resin
By placing paper, coating carbamate and opening fibers to treat raw material pulp, highly dispersible carbamate microfiber cellulose was obtained. Combined with maleic anhydride modified resin, the poor dispersion of cellulose microfibers in the resin was solved. The problem of this has achieved a significant improvement in the strength of the composite resin.
Patent Information
- Application Number
- CN202380052143.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-06-06
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively inhibit the aggregation of cellulose microfibers, resulting in poor dispersion in the resin and the inability to sufficiently improve the strength of the composite resin.
By papermaking and coating the raw material pulp with urethane, a urethane-esterified pulp sheet was formed, and urethane was obtained through the fiber opening process with a fineness A of more than 25% and a fibrillation rate of less than 1.0% by fibrillation rate of less than 1.0% by fiber opening process. Esterified microfibrous cellulose, combined with maleic anhydride modified resin, is used to make a fibrous cellulose composite resin.
The uniform dispersion of cellulose microfibers in the resin is achieved, the strength of the composite resin is significantly improved, and the strength decrease caused by fiber aggregation is avoided.
Smart Images

Figure CN119522254A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a fibrous cellulose composite resin, a fibrous cellulose-containing material, and a method for producing the fibrous cellulose composite resin. Background Art
[0002] In order to improve the strength of the resin, various resins such as PP (polypropylene), PE (polyethylene), and ABS (acrylonitrile, butadiene, and styrene copolymer resin) sometimes contain microfibers such as microfiber cellulose obtained by fibrillating pulp as a reinforcing material (filler). However, the microfibers tend to aggregate during the drying process, and once aggregated, they sometimes cannot be decomposed under the shear applied during mixing with the resin and remain in the form of aggregates. If the microfibers remain in the form of aggregates, they not only cannot function as a reinforcing material, but may also reduce the strength of the resin.
[0003] On the other hand, if fibers whose pulp fibrillation is suppressed are used as reinforcing materials, the dispersibility of the fibers is improved, but the fibers no longer form a three-dimensional network in the resin, and the strength of the resin may not be sufficiently improved.
[0004] In this regard, there is also a proposal to replace the hydroxyl groups of microfibers with carbamate groups, which is proposed to improve the dispersibility of microfibers, focusing on the fact that microfibers are hydrophilic and resins are hydrophobic (e.g., Patent Document 1). However, although this proposal is very useful in improving the dispersibility of uncoagulated microfibers in resins, it is not very effective in improving the dispersibility of temporarily coagulated microfibers. Therefore, it is urgently desired to develop a method for producing a fibrous cellulose composite resin with high strength by suppressing the coagulation of microfibers as much as possible to improve the dispersibility of microfibers in resins.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-1876 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The problem to be solved by the present invention is to provide a fibrous cellulose composite resin having high strength, a fibrous cellulose-containing material, and a method for producing a fibrous cellulose composite resin having high strength.
[0010] Means for solving problems
[0011] The inventors of the present invention believed that fine fibers such as microfiber cellulose are easily aggregated during the drying process, and therefore the shape of the fibers after fibrillation is greatly affected, and conducted in-depth research based on this premise. As a result, it was found that even for fine fibers of the same fiber size, the more branched parts there are, and more specifically, even for fine fibers with the same fineness A, the greater the fibrillation rate of the fine fibers, the more firmly the branched parts of the fibers aggregate with each other during the drying process. Based on this discovery, the following means for solving the above-mentioned problems were conceived.
[0012] That is, a fibrous cellulose composite resin characterized by:
[0013] Contains fibrous cellulose and resin,
[0014] The fibrous cellulose is carbamate-modified microfibril cellulose in which a part or all of the hydroxyl groups are substituted with carbamate groups, the fineness A is 25% or more, and the fibrillation rate is 1.0% or less.
[0015] In addition, a method for producing a fibrous cellulose composite resin is characterized in that:
[0016] Raw pulp is made into paper to form a strip-shaped pulp sheet.
[0017] At least one of urea and a urea derivative is applied to the pulp sheet and heated to prepare a urethanized pulp sheet.
[0018] The urethanized pulp sheet is opened to prepare urethanized microfiber cellulose having a fineness A of 25% or more and a fibrillation rate of 1.0% or less.
[0019] The urethanized microfiber cellulose and a resin are kneaded to prepare a fibrous cellulose composite resin.
[0020] In addition, a fibrous cellulose-containing material is characterized by comprising:
[0021] Carbamate-modified microfiber cellulose in which a part or all of the hydroxyl groups are substituted with carbamate groups, the fineness A is 25% or more, and the fibrillation rate is 1.0% or less; and
[0022] Maleic anhydride modified resin.
[0023] Effects of the Invention
[0024] According to the present invention, there are provided a fibrous cellulose composite resin having high strength, a fibrous cellulose-containing material, and a method for producing a fibrous cellulose composite resin having high strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is an explanatory diagram of the steps of obtaining urethanized fine fibers from raw material pulp. DETAILED DESCRIPTION
[0026] Next, a specific embodiment will be described. It should be noted that this embodiment is an example of the present invention, and the scope of the present invention is not limited to the scope of this embodiment.
[0027] The fibrous cellulose composite resin of the present embodiment comprises fibrous cellulose and a resin, wherein the fibrous cellulose is a carbamate-modified microfiber cellulose in which a part or all of the hydroxyl groups are substituted with carbamate groups, the fineness A is 25% or more, and the fibrillation rate is 1.0% or less. In the present embodiment, the carbamate-modified microfiber cellulose can be obtained by carbamate-modifying the raw pulp and fibrillating it. In this regard, there is no particular limitation on the method by which the carbamate-modified microfiber cellulose has the above-mentioned physical properties. Among them, it is preferred that the raw pulp is paper-made to form a strip-shaped pulp sheet, at least any one of urea and a urea derivative is applied to the pulp sheet and heated to form a carbamate-modified pulp sheet, and the carbamate-modified pulp sheet is fibrillated. Therefore, the following description is made according to this production method.
[0028] like Figure 1 As shown, the manufacturing method of this embodiment can be mainly divided into: a step X1 to obtain a cellulose fiber-containing material P2 that can be used as a "pulp sheet containing at least any one of urea and urea derivatives (also referred to as "urea, etc.")" from a raw pulp P1; a step X2 to obtain carbamate-treated cellulose fibers P3 by reacting urea, etc. after the step X1; and a step X3 to obtain carbamate-treated fine fibers P4 by opening the carbamate-treated cellulose fibers P3 after the step X2.
[0029] The step X1 to obtain the cellulose fiber-containing material P2 can be mainly divided into a papermaking step 100 of making a strip-shaped pulp sheet from the raw material pulp P1 and a coating step 200 of coating the pulp sheet with urea or the like. These steps will be described below in order.
[0030] (Raw pulp)
[0031] As the raw material pulp P1, for example, one or more kinds can be selected from wood pulp made from broad-leaved trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fiber, etc., and waste paper pulp (DIP) made from recycled waste paper, broken paper, etc.
[0032] In order to avoid the mixing of impurities as much as possible, wood pulp is preferably used as the raw material pulp P1. As the wood pulp, for example, one or more kinds of chemical pulps such as broadleaf kraft pulp (LKP) and coniferous kraft pulp (NKP), mechanical pulp (TMP), etc. can be selected and used.
[0033] The hardwood kraft pulp may be hardwood bleached kraft pulp, hardwood unbleached kraft pulp, or hardwood semi-bleached kraft pulp. Similarly, the conifer kraft pulp may be conifer bleached kraft pulp, conifer unbleached kraft pulp, or conifer semi-bleached kraft pulp.
[0034] Among them, it is preferred to use NKP (preferably NBKP) and LKP (preferably LBKP) together. In this regard, the cellulose fibers of NKP are thick and long, so the strength of the cellulose fiber content is improved, but the texture is deteriorated. On the other hand, the cellulose fibers of LKP are thin and short, so the strength of the pulp sheet is reduced during papermaking, but the texture is improved. Based on such characteristics, when NKP and LKP are used together, the mixing ratio of NKP is preferably 1 to 99% by mass, more preferably 5 to 95% by mass, and particularly preferably 10 to 90% by mass. If the mixing ratio of NKP is less than 10% by mass, paper breaks may occur due to insufficient tensile strength and tear strength during the papermaking process and the coating process. On the other hand, if the mixing ratio of NKP exceeds 90% by mass, that is, if the mixing ratio of LKP is less than 10% by mass, it may not be possible to fully obtain characteristics such as the reinforcing effect of the resin.
[0035] On the other hand, as mechanical pulp, for example, one or more kinds can be selected from stone ground pulp (SGP), pressure stone ground pulp (PGW), wood ground pulp (RGP), chemical fine grinding pulp (CGP), thermogrind pulp (TGP), grinding pulp (GP), thermomechanical pulp (TMP), chemical thermomechanical pulp (CTMP), disc mechanical pulp (RMP), bleached thermomechanical pulp (BTMP) and the like.
[0036] The freeness of the raw pulp P1 measured in accordance with JIS P 8121-2 is preferably 200 to 700 cc, more preferably 250 to 650 cc, and particularly preferably 300 to 600 cc. If the freeness is less than 200 cc, dehydration in the wire section described later is poor, and the papermaking speed may not be increased. On the other hand, if the freeness exceeds 700 cc, the texture is poor, and the paper may break in the subsequent coating step.
[0037] In the raw pulp P1, it is preferred to add a sizing agent internally and / or externally as needed to adjust the Stokes sizing degree (JIS P 8122) and the Cobb sizing degree (JIS P 8140). In this regard, the Stockigt sizing degree is a test for measuring the time required for a reagent to penetrate into a pulp sheet and develop color, and the lower the value, the higher the permeability. On the other hand, the Cobb sizing degree is a test for measuring the amount of water (mass) absorbed when one side of a pulp sheet is in contact with water for a certain period of time, and the higher the value, the higher the water absorption. Therefore, the Stockigt sizing degree as an indicator of permeability and the Cobb sizing degree as an indicator of water absorption are greatly different in the case where a sizing agent is included and the case where a sizing agent is not included. However, if the amount of the sizing agent is large, the amount of urea or the like added (penetration amount) in the coating step described later is insufficient, and the reaction may become insufficient. On the other hand, if the amount of the sizing agent is small, paper breakage may occur due to reduced wet paper strength. Therefore, the amount of the sizing agent added needs to be adjusted, and this amount can be based on the Stockigt sizing degree or the Cobb sizing degree of the pulp sheet before coating with urea or the like.
[0038] Specifically, the Stockigt sizing degree measured in accordance with JIS P 8122 is preferably 0.1 to 100 seconds, more preferably 0.2 to 80 seconds, and particularly preferably 0.5 to 50 seconds. In addition, the Cobb sizing degree (10 seconds) measured in accordance with JIS P 8140 is preferably 10 to 600 g / m 2 , more preferably 20 to 580 g / m 2 , particularly preferably 30 to 550 g / m 2 .
[0039] The ash content of the raw material pulp P1 measured in accordance with JIS P 8251 is preferably 0 to 20 mass %, more preferably 0 to 15 mass %, and particularly preferably 0 to 10 mass %. If the ash content exceeds 20 mass %, the strength of the wet pulp sheet decreases, and paper breakage may occur particularly in the coating step.
[0040] It should be noted that the manufacturing method of this embodiment is not a method for manufacturing paper, but only utilizes the state or form of a pulp sheet in order to efficiently react urea, etc. Therefore, the knowledge related to ash addition in paper manufacturing technology cannot be directly utilized. For example, when fiber opening is performed in a subsequent process, it is also necessary to consider the influence of the amount of ash on the fiber opening process.
[0041] (Papermaking process)
[0042] In the manufacturing method of this embodiment, raw material pulp P1 is paper-made to form a strip-shaped pulp sheet in the papermaking step 100. Here, the strip-shaped refers to a continuous elongated sheet having a predetermined width (e.g., 300 to 10,000 mm), and refers to a shape that is the same or similar to wet paper or paper web in the paper manufacturing process.
[0043] Examples of papermaking equipment used in the papermaking step 100 include a Fourdrinier former having a wire section 110, a press section 120, etc., a former in which an on top former is combined with a Fourdrinier former, and a gap former.
[0044] Among them, the use of a gap former in which the stock jet ejected from the headbox is immediately sandwiched between two wires has the advantage that the difference between the front and back is small and urea etc. can be uniformly infiltrated into the pulp sheet in the thickness direction (Z-axis direction) of the pulp sheet.
[0045] However, although the sandwich former has the advantage of small difference between the front and the back, it has poor flatness because both sides are mesh surfaces. In addition, the texture is determined at the moment when the paper material is blown onto the mesh, so it has the characteristics of poor texture. In this method, since the production of paper itself is not the purpose, flatness and texture may not be a problem, but from the perspective of the relationship with the coating method in the later stage and the relationship with the permeability of the reagent, it is preferred to use a fourdrinier with an on top former because the flatness and texture are excellent. In particular, if a shaking device (a device that shakes the mesh horizontally) is installed on the mesh, the texture is further improved, which is preferred.
[0046] The pulp sheet (paper layer) of the wire section 110 flows to (is transferred to) the press section 120 and is dehydrated.
[0047] The press used in the press section 120 may be, for example, a straight type, an inverted type, a reverse type, or a combination thereof. Of these, the straight type without open traction is preferred because it is easy to hold the pulp sheet and has fewer operational problems such as paper breaks.
[0048] The pulp sheet (wet paper) that has passed through the press section 120 can be transferred to a single-layer or double-layer pre-drying section 130 for drying. The pre-drying section 130 is preferably a single-layer dryer of a non-open traction type, because it reduces paper breakage and can be dried efficiently without reducing the volume.
[0049] The drying temperature in the pre-drying section 130 is preferably 80 to 140° C., more preferably 85 to 135° C., and particularly preferably 90 to 130° C. If the drying temperature exceeds 140° C., partial overdrying occurs, and the penetration of urea or the like in the coating step 200 may be poor in the overdried portion. On the other hand, if the drying temperature is lower than 80° C., partial poor drying occurs, and paper breakage may occur in the poorly dried portion.
[0050] The moisture content of the pulp sheet after the pre-drying section 130 is preferably 0.1 to 10%, more preferably 1 to 9%, and particularly preferably 2 to 8%. If the moisture content is less than 0.1%, the pulp sheet is too dry and the penetration of urea or the like in the coating step 200 may be poor. On the other hand, if the moisture content exceeds 10%, the pulp sheet is poorly dried and paper breakage may occur in the coating step 200.
[0051] In this form, the said water content is the value measured by infrared ray using a BM meter (basis weight / water content).
[0052] The tape-shaped pulp sheet obtained in the papermaking step 100 preferably has a basis weight of 60 to 800 g / m2 as measured in accordance with JIS P 8124. 2 , more preferably 80 to 750 g / m 2 , particularly preferably 100 to 700 g / m 2 If the basis weight is less than 50g / m 2 If the basis weight exceeds 800 g / m 2 urea etc. may not be able to fully penetrate in the coating step 200. It should be noted that the above basis weight is for a single-layer papermaking. If a multi-layer papermaking is performed with two or more layers, the reagent may remain at the interface of the layer.
[0053] Urea or the like applied in the coating step 200 may contain any papermaking reagent. There is no limitation on the type of papermaking reagent, and the concentration of the papermaking reagent may be appropriately adjusted as needed. However, it is necessary not to damage the purpose of applying urea or the like, and sometimes it is necessary to make adjustments. For example, in the present embodiment in which urea or the like is used in the coating step 200, in the papermaking step 100, papermaking is performed in such a manner that the concentration of papermaking reagents such as various starches, CMC (carboxymethyl cellulose) having a hydroxyl group, colloidal silica, aluminum sulfate, etc. having a silanol group or the like bonded to a certain element with -OH groups, rosin sizing agents, ASA (alkenyl succinic anhydride), AKD (alkyl ketene dimer), various starches, CMC, etc. is preferably 0 to 10%, more preferably 0.1 to 9%, and particularly preferably 0.2 to 8%. Since the above papermaking reagents are subjected to modification reactions caused by urea or the like, if the above papermaking reagents are contained in large amounts, the use of urea or the like in the reaction step X2 will be hindered accordingly. The above reagents do not depend on internal or external addition.
[0054] On the other hand, the dye is determined by the subsequent use. For example, when the use is a resin reinforcement material and coloring of the fine fibers is not preferred, papermaking is performed with the dye preferably at 0 to 10%, more preferably 0.1 to 5%, and particularly preferably 0.2 to 3%.
[0055] From the same viewpoint, the pulp sheet preferably has a whiteness of 80% or more, more preferably 82% or more, and particularly preferably 85% or more as measured in accordance with JIS P 8148. When LBKP and NBKP are used as the raw material pulp P1 as in the above example, the whiteness is usually 80% or more, and there is no need to adjust the whiteness.
[0056] The tensile strength of the pulp sheet measured in accordance with JIS P 8113 is preferably 10 MPa or more, more preferably 15 MPa or more, and particularly preferably 20 MPa or more. When the tensile strength is less than 10 MPa (1 kN / m, thickness 100 μm), paper breakage may occur in the coating step 200. However, although the tensile strength increases when the basis weight is increased, as described above, if the basis weight is increased, urea and the like are difficult to penetrate in the coating step 200. Therefore, the balance between the tensile strength and the basis weight is also important, and the specific tensile strength (tensile strength / basis weight) is preferably 1 to 10000 Nm / g, more preferably 5 to 5000 Nm / g, and particularly preferably 10 to 1000 Nm / g.
[0057] On the other hand, the wet paper strength of the pulp sheet measured in accordance with JIS P 8135 is preferably 0.1 kN / m or more, more preferably 0.2 kN / m or more, and particularly preferably 0.5 kN / m or more. When the wet paper strength is less than 0.1 kN / m, paper breakage may occur in the coating step 200. However, although the wet paper strength is increased when the basis weight is increased, as described above, it is difficult for urea and the like to penetrate in the coating step 200 when the basis weight is increased. Therefore, the balance between the wet paper strength and the basis weight is also important, and the specific wet paper strength (wet paper strength / basis weight) is preferably 0.1 to 5000 Nm / g, more preferably 0.5 to 1000 Nm / g, and particularly preferably 1 to 500 Nm / g.
[0058] (Coating process)
[0059] The pulp sheet dried in the pre-drying section 130 is coated with urea or the like in the coating section 210 between the pre-drying section 220 and the post-drying section 220. Here, in this specification, "coating" only refers to the "coating" behavior, and is not intended to limit the state of the urea or the like after coating. Therefore, for example, in addition to the mode in which the urea or the like remains on the surface of the pulp sheet to form a coating layer, the mode in which the urea or the like completely penetrates into the pulp sheet and does not form a coating layer on the surface of the pulp sheet, that is, the mode in which the urea or the like is only in the impregnation state, is also included.
[0060] In the coating section 210, urea or the like can be coated by coating methods such as bevel blade coating, size press coating, tough blade coating, rod coating, impregnation coating, spray coating, and comma blade coating. Among them, the coating in the coating section 210 is preferably performed by tough blade coating. In this regard, tough blade coating is a type of blade coating, and in bevel blade coating, which is also a type of blade coating, urea or the like sprayed from an injector is scraped off, while in tough blade coating, urea or the like is pressed into the pulp sheet while coating. Therefore, this method is suitable for the present method in which it is highly necessary to make urea or the like penetrate into the pulp sheet.
[0061] On the other hand, the impregnation coating and the comma blade coating each have the following characteristics.
[0062] That is, first, in this method, the impregnation method refers to a method of coating by moving the pulp sheet in a container filled with urea, etc. In addition, the comma blade coating refers to a method of coating by forming a liquid pool between two rollers and a blade and moving the pulp sheet between the gaps to adjust the coating amount.
[0063] The concentration of urea or the like can be appropriately adjusted as needed. In the present embodiment of carbamate formation, it is preferably 20 to 50% by mass, more preferably 25 to 45% by mass, and particularly preferably 30 to 40% by mass. If the concentration of urea or the like is less than 20% by mass, the carbamate formation rate is insufficient and drying may be difficult. On the other hand, if the concentration of urea or the like exceeds 50% by mass, when urea water is prepared, the temperature of the solution decreases due to the endothermic reaction caused by the dissolution of urea or the like, and urea or the like may precipitate.
[0064] The viscosity of urea water (40% concentration) measured in accordance with JIS-Z8803 (2011) is preferably 2000 cps or less, more preferably 1700 cps or less, and particularly preferably 1500 cps or less. If the viscosity exceeds 2000 cps, urea water will have difficulty penetrating into the pulp sheet.
[0065] In the production method of this embodiment, the coating step 200 can be performed offline or online. However, when the production speed is 300 m / min or more, it is preferred to sequentially introduce the papermaking step 100 and the coating step 200 as continuous processes in the machine (online). If the on-line method is adopted, the production efficiency is improved, and the coating can be uniformly applied without being affected by the storage state of the pulp sheet.
[0066] In the production method of this embodiment, urea or the like may be applied to only one side of the pulp sheet or to both sides, but it is preferred to apply it to both sides from the viewpoint of uniformity of the reaction performed in the subsequent step.
[0067] When urea or the like is applied to both sides of a pulp sheet in an off-line manner, there is an advantage that the coating amount can be made different between the front and back sides according to the characteristics of the pulp sheet.
[0068] The coating mass ratio of urea, etc. to cellulose fibers (urea, etc. / cellulose fibers) is preferably 10 to 400 kg / pt (pulp ton), more preferably 20 to 300 kg / pt, and particularly preferably 45 to 200 kg / pt. If the coating mass ratio is less than 45 kg / pt, urethane formation may not proceed sufficiently. On the other hand, if the coating mass ratio exceeds 200 kg / pt, the coating is excessive, and the remaining urea, etc. may adhere to the device. It should be noted that, generally, the coating amount is per 1 m 2 However, in the present embodiment, since urea or the like is a reagent (reaction reagent) for reacting with cellulose fibers, it is preferably specified by the amount of urea per unit mass of cellulose fibers.
[0069] The pulp sheet having passed through the coating section 210 enters the post-drying section 220 to be dried.
[0070] In the drying of the post-drying section 220, for example, a hot air drying device, a gas heater drying device, an infrared drying device, or the like can be used. However, if an infrared drying device is used, urea or the like is solidified on the surface layer of the pulp sheet, which may hinder the penetration of urea or the like. Therefore, it is preferable to use a hot air drying device. In particular, the hot air drying device is easy to control the temperature, so if a multi-stage hot air drying device is provided and designed in a manner that the temperature is gradually increased, drying can be performed without hindering the penetration of urea or the like.
[0071] In the post-drying section 220, the drying temperature is preferably 80 to 140°C, more preferably 85 to 135°C, and particularly preferably 90 to 130°C. If the drying temperature is lower than 80°C, the drying may be insufficient when the drying time is short, so it is not suitable for high-speed production. On the other hand, if the drying temperature exceeds 140°C, by-products such as urea may be generated.
[0072] The moisture content of the pulp sheet after passing through the post-drying unit 220 is preferably 0 to 10%, more preferably 0 to 8%, and particularly preferably 0 to 7%. If the moisture content exceeds 10%, the reaction efficiency may decrease in the reaction step.
[0073] In this step, the moisture content is a value measured by infrared light using a BM meter (basis weight / water content).
[0074] The surface temperature of the pulp sheet after passing through the post-drying section 220 is preferably 30 to 95° C., more preferably 35 to 90° C., and particularly preferably 40 to 85° C. If the surface temperature is lower than 40° C., drying may be insufficient. On the other hand, if the surface temperature exceeds 95° C., byproducts may be generated from the reaction reagents.
[0075] It should be noted that in this method, the production of paper itself is not the purpose, but the form of paper (pulp sheet) is only temporarily utilized, so the calendering step may be performed later, or the calendering step may be omitted and the reaction step may be performed.
[0076] (Urea-forming step)
[0077] The pulp sheet (pulp fiber content) that has passed through the post-drying section 220 may be temporarily wound up in a winding section (not shown) and stored as a winding stock. Afterwards, the winding stock may be heated, cooled, or the like in a wound state to react urea or the like with the cellulose fibers, but in the present embodiment, the pulp sheet is pulled out from the winding stock and treated to be urethanized.
[0078] When the drawn pulp sheet is temporarily made into a winding material, it is preferred to dry it to a moisture content of 10% by mass or less, more preferably 9% by mass or less, and particularly preferably 8% by mass or less. This drying is performed to improve the reaction efficiency.
[0079] However, the manufacturing efficiency is reduced when the method of temporarily forming a coiled blank as described above is used. Therefore, the pulp sheet passing through the post-drying section 220 is preferably directly continuously entered (transferred) to the urethanization step X2. In this case, the above drying of the pulp sheet before urethanization can be omitted.
[0080] In the urethanization step X2, urea and the like contained in the pulp sheet, that is, the cellulose fiber-containing material, are reacted with the cellulose fibers. This reaction will be described in detail.
[0081] First, carbamate modification refers to modifying cellulose fibers into cellulose fibers having carbamate groups. In other words, it means that cellulose fibers are brought into a state where carbamate (ester of carbamic acid) is introduced.
[0082] The carbamate group is a group represented by -O-CO-NH-, for example, a group represented by -O-CO-NH2, -O-CONHR, -O-CO-NR2, etc. That is, the carbamate group can be represented by the following structural formula (1).
[0083] [Chemistry 1]
[0084]
[0085] Here, n represents an integer greater than 1. Each R is independently hydrogen, a saturated straight-chain hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated straight-chain hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, and at least one of derivatives thereof. In addition, cross-linked carbamate cellulose having a cross-linked structure formed between cellulose molecules or fibers by carbamate groups can be cited.
[0086] Examples of the saturated straight-chain hydrocarbon group include straight-chain alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, and a propyl group.
[0087] Examples of the saturated branched hydrocarbon group include branched alkyl groups having 3 to 10 carbon atoms, such as isopropyl, sec-butyl, isobutyl and tert-butyl.
[0088] Examples of the saturated cyclic hydrocarbon group include cycloalkyl groups such as cyclopentyl, cyclohexyl and norbornyl.
[0089] Examples of the unsaturated straight-chain hydrocarbon group include straight-chain alkenyl groups having 2 to 10 carbon atoms such as vinyl, propen-1-yl and propen-3-yl, and straight-chain alkynyl groups having 2 to 10 carbon atoms such as ethynyl, propyn-1-yl and propyn-3-yl.
[0090] Examples of the unsaturated branched hydrocarbon group include branched alkenyl groups having 3 to 10 carbon atoms such as propen-2-yl, buten-2-yl and buten-3-yl, and branched alkynyl groups having 4 to 10 carbon atoms such as butyn-3-yl.
[0091] Examples of the aromatic group include a phenyl group, a tolyl group, a xylyl group, and a naphthyl group.
[0092] Examples of derivative groups include groups in which one or more hydrogen atoms possessed by the above-mentioned saturated straight-chain hydrocarbon groups, saturated branched hydrocarbon groups, saturated cyclic hydrocarbon groups, unsaturated straight-chain hydrocarbon groups, unsaturated branched hydrocarbon groups and aromatic groups are replaced by substituents (e.g., hydroxyl groups, carboxyl groups, halogen atoms, etc.).
[0093] In cellulose fibers having carbamate groups (carbamate introduced therein), part or all of the hydroxyl groups with high polarity are replaced by carbamate groups with relatively low polarity. Therefore, the hydrophilicity of the cellulose fibers is low, and the affinity with resins with low polarity is high. As a result, the fine fibers obtained by fibrillating the cellulose fibers have characteristics such as excellent uniform dispersibility with the resin. In addition, the slurry of the fine fibers has low viscosity and good handling properties.
[0094] The lower limit of the degree of substitution of the hydroxyl groups of the cellulose fiber by the carbamate groups is preferably 0.05, more preferably 0.1, and particularly preferably 0.2. If the degree of substitution is 0.05 or more, the effect of the introduction of the carbamate can be surely exerted. On the other hand, the upper limit of the degree of substitution is preferably 1, more preferably 0.5, and particularly preferably 0.4. In this regard, cellulose fibers with a high degree of substitution have the problem of being expensive.
[0095] It should be noted that cellulose is a polymer with anhydroglucose as a structural unit, and each structural unit has three hydroxyl groups. Therefore, if all hydroxyl groups are replaced by carbamate groups, the degree of substitution is 3.
[0096] The amount of carbamate groups introduced into the cellulose fibers is preferably 0.5 to 4.5 mmol / g, more preferably 0.6 to 4.0 mmol / g, and particularly preferably 0.7 to 3.5 mmol / g. If the substitution rate is less than 0.5 mmol / g, sufficient reinforcing effect may not be obtained when compounded with a resin. On the other hand, if the introduction amount exceeds 4.5 mmol / g, an excessive amount of urea may be required.
[0097] Regarding the introduction of carbamate into cellulose fibers (carbamate treatment), there are two methods: carbamate treatment of cellulose fibers followed by micronization, and a method of micronizing cellulose fibers to make microfibers followed by carbamate treatment. However, it is preferred to first perform carbamate treatment and then perform fiber opening as in the present embodiment. This is because the dehydration efficiency of cellulose fibers before fiber opening is high, and the cellulose fibers are easily opened by the heating accompanying carbamate treatment.
[0098] Conventionally, the process of carbamateizing cellulose fibers includes, for example, a mixing process, a removing process, a heating process, etc. In the mixing process, cellulose fibers and urea or the like are mixed in a dispersion medium. However, if this process is added, the production efficiency is significantly reduced. Therefore, in this method, urea or the like is reacted with cellulose fibers in the form of a strip-shaped pulp sheet. At this time, the pulp sheet can be considered to be in the form of a winding stock or in the form of a pulled-out pulp sheet, but in terms of excellent reaction efficiency and reaction uniformity, it is in the pulled-out state.
[0099] As urea and urea derivatives, for example, urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, compounds obtained by replacing the hydrogen atoms of urea with alkyl groups, etc. can be used. These ureas or urea derivatives can be used alone or in combination. Among them, urea is preferably used.
[0100] In the carbamate-forming step X2 of the present embodiment, a pulp sheet, i.e., a cellulose fiber-containing material P2 including urea or the like, is subjected to a heat treatment. In the carbamate-forming step X2, a part or all of the hydroxyl groups of the cellulose fibers react with urea or the like and are replaced with carbamate groups. More specifically, when urea or the like is heated, it is decomposed into isocyanic acid and ammonia as shown in the following reaction formula (1). Moreover, the reactivity of isocyanic acid is very high, and, for example, as shown in the following reaction formula (2), it forms carbamate with the hydroxyl groups of cellulose.
[0101] NH2-CO-NH2→HN=C=O+NH3…(1)
[0102] Cell-OH+HN=C=O→Cell-O-CO-NH2…(2)
[0103] When urea or the like is reacted with cellulose fibers, the heating temperature in the urethanization step X2 is preferably 150 to 280° C., more preferably 160 to 270° C., and particularly preferably 180 to 260° C. If the heating temperature is lower than 150° C., sufficient reaction may not occur. On the other hand, if the heating temperature exceeds 280° C., urea or the like may be thermally decomposed, and coloring may become significant.
[0104] When urea or the like is reacted with cellulose fibers, the heating time in the urethanization step X2 is preferably 1 to 60 seconds, more preferably 1 to 30 seconds, and particularly preferably 1 to 20 seconds. If the heating time exceeds 60 seconds, coloring may become significant and productivity may be poor.
[0105] As described above, the pulp sheet may be heated directly in a wound state or may be pulled out from a wound billet and heated. When the pulp sheet is heated directly in a wound state, a hot air heating method, a high frequency heating method, a rotary kiln method, etc. may be used as the heating device. On the other hand, when the pulp sheet is pulled out from a wound billet and heated, an induction heating roller, an oil heating roller, hot air heating, far infrared heating, microwave heating, etc. may be used as the heating device.
[0106] Here, the characteristics when the above heating device is used will be described.
[0107] First, the heating method is roughly divided into two types (intermittent type and continuous type (roll-to-roll type)). In the intermittent type, there are high-frequency heating devices and rotary kilns, which are equipment that can react a large number of samples at a time. In this regard, in the high-frequency heating device, when the object to be heated is placed in the electrode, polarization is caused inside the heated object to generate electric charge, and due to the speed change of the frequency, the molecules undergo intense internal friction and are heated. On the other hand, the rotary kiln is a rotating high-temperature firing device, and is used in the reagent recovery process of the kraft pulping process in the papermaking industry.
[0108] On the other hand, in the roll-to-roll type in which the pulp sheet is heated by passing it between a pair of rollers, in order to continuously heat the pulp sheet coated with urea, there are induction heating rollers, oil heating rollers, and hot air heating, far infrared heating, and microwave heating that can perform continuous heating. In this regard, the induction heating roller is a method of heating the roller itself by the action of an electrically generated magnetic field, and is also used in calendering equipment in the papermaking process. In addition, the oil heating roller is a method of heating the roller surface by circulating heated oil inside the roller. In addition, hot air heating is a method of spraying hot air from nozzles arranged above and below the conveyor belt to the upper and lower surfaces of the pulp sheet to heat the pulp sheet passing therebetween. In addition, far infrared heating is a method of radiating infrared rays with a wavelength of 3μm to 1mm and utilizing contraction and angular motion between atoms to perform heating. In addition, microwave heating is a method of generating heat by utilizing the phenomenon of frictional heat generated between molecules constituting the pulp sheet according to the frequency (300MHz to 30GHz), and microwave ovens are generally used.
[0109] Compared with oil-type heating rollers, reaction equipment using induction heating rollers is preferred because of their high reaction efficiency and energy efficiency. On the other hand, intermittent heating using the state of coiling the billet, especially heating using high frequency, causes uneven reaction because a large amount of sample is heated at one time, making it difficult to perform a uniform urethane reaction.
[0110] On the other hand, in continuous heating other than roll-to-roll heating such as induction heating rolls and oil heating rolls, or non-contact heating methods such as hot air heating and far infrared heating, the urethanization reaction can be advanced by increasing the reaction temperature.
[0111] As a conclusion, it can be said that it is particularly preferable to pass a strip-shaped pulp sheet containing urea or the like made by papermaking raw material pulp P1 between a pair of rolls and heat it, and to react by the heating. Among them, when the sheet width of the pulp sheet is 300 to 1000 mm, it is more preferable that at least one of the pair of rolls is a heating roll. In this case, the heating temperature of the heating roll is preferably 180 to 280°C, more preferably 200 to 270°C, and particularly preferably 220 to 260°C.
[0112] In addition, it is preferred to configure the system in multiple stages (two or more pairs of rollers), suppress the heating temperature of the first stage to 80 to 140°C (more preferably 90 to 120°C), and set the heating temperature of the second and subsequent stages to 180 to 280°C (more preferably 200 to 280°C). In addition, it is also possible to configure the system as follows: the heating temperature of each heating roller is set between 80 and 280°C, and the heating temperature is increased stepwise. In this case, instead of setting the first stage to a low temperature as described above, it is also preferred to set the clamping line pressure of the pair of rollers of at least one stage to 1 to 100,000 N / cm, preferably 10 to 50,000 N / cm. It should be noted that according to the above configuration, there is an advantage that the shrinkage of the pulp sheet can be suppressed.
[0113] The mixture after the heating treatment may be washed. The washing may be performed with water or the like. The unreacted and remaining urea or the like can be removed by the washing.
[0114] Here, whether the washing is sufficiently performed can be confirmed by measuring the nitrogen concentration and transparency of the filtrate (slurry), and it is preferably evaluated by the "replacement washing rate" defined below. It should be noted that the "initial stage" below refers to the first supply of the pulp slurry before dehydration (after dissociation) to the dehydration process. In addition, "after the second stage" means that the above-mentioned initial stage is completed, and the same dehydration process is performed again after adding dilution water and stirring.
[0115] Replacement cleaning rate D0 (initial stage) = (A0) / (X0+Y0)×100(%)
[0116] X0: Amount of water contained in the pulp before dehydration = Amount of pulp water dispersion before dehydration - Pulp concentration before dehydration × Amount of pulp water dispersion before dehydration
[0117] Y0: Amount of water contained in the dehydrated pulp = Amount of dehydrated pulp water dispersion - Dehydrated pulp concentration × Amount of dehydrated pulp water dispersion
[0118] A0: Filtrate volume after dehydration = X0-Y0
[0119] Replacement cleaning rate Dn (after the second stage) = Dn-1 + An × (1-Dn-1) / (Xn + Yn) × 100 (%)
[0120] Dn-1: Replacement cleaning rate of the previous stage
[0121] Xn: Amount of water contained in the pulp before dehydration = Amount of pulp water dispersion before dehydration - Pulp concentration before dehydration × Amount of pulp water dispersion before dehydration
[0122] Yn: Amount of water contained in the dehydrated pulp = Amount of dehydrated pulp water dispersion - Dehydrated pulp concentration × Amount of dehydrated pulp water dispersion
[0123] An: The amount of filtrate after dehydration = Xn-Yn
[0124] In this embodiment, the replacement cleaning rate is preferably 80% or more. If it is difficult to achieve a cleaning rate of 80% or more by one dehydration cleaning, it is preferred to repeat the dehydration cleaning several times until the cleaning rate reaches 80% or more, and then perform dilution dehydration cleaning.
[0125] The fineness A of the urethane cellulose fibers P3 obtained as described above is preferably 10 to 40%, more preferably 15 to 35%, and particularly preferably 20 to 30%. By increasing the fineness of the fibers before fiber opening, the fibrillation rate of the fibers after the fiber opening step can be easily reduced.
[0126] It should be noted that in order to avoid paper breakage in the papermaking process, it is preferred to slightly open the pulp before papermaking. If the opening is performed in advance, the fineness A of the fiber after papermaking is increased. Therefore, in order to increase the fineness A of the fiber after papermaking, if the fiber before papermaking is opened in advance to reduce the freeness, it is not only easy to reduce the fibrillation rate of the final fiber, but also can reduce paper breakage in the manufacturing process. From this aspect, the freeness of the fiber before papermaking is preferably 100 to 800 ml, more preferably 200 to 750 ml, and particularly preferably 300 to 700.
[0127] The freeness is a value measured in accordance with JIS P8121-2 (2012).
[0128] (Fiber opening process)
[0129] In this embodiment, the urethanized cellulose fibers P3 obtained as described above are pulverized as necessary and then opened (refined) in the fiber opening step X3. The fiber opening yields urethanized fine fibers P4.
[0130] In addition, in this form, fine fiber means the cellulose fiber whose average fiber width is 0.01-19 micrometers. For example, fine fiber includes microfibril cellulose (microfibrillated cellulose) and cellulose nanofiber.
[0131] In addition, the carbamate-modified cellulose fibers P3 may be opened immediately after being crushed, but it is preferred that the sheet-like or crushed reactive cellulose fibers P3 be dissociated in water before being opened, and then dehydrated using a dehydrating device such as a valveless filter to clean the reactive cellulose fibers P3. In addition, when a valveless filter is used for dehydration, spraying the dehydrated mat-like reactive cellulose fibers P3 can make cleaning more complete. By cleaning, unreacted reaction liquid, by-products of the reaction liquid, or water-soluble impurities can be removed.
[0132] In the present embodiment, microfiber cellulose refers to fibers having an average fiber diameter that is thicker than cellulose nanofibers. Specifically, for example, it is 0.1 to 19 μm, preferably 0.2 to 10 μm. If the average fiber diameter of the microfiber cellulose is lower than (less than) 0.1 μm, there is no change compared to the cellulose nanofibers. For example, when mixed with a resin, the effect of improving the strength (especially the bending modulus) of the resin may not be fully obtained. In addition, the fiber opening time becomes longer and a large amount of energy is required. In addition, the dehydration of the cellulose fiber slurry deteriorates. If the dehydration deteriorates, a large amount of energy is required for drying. If a large amount of energy is applied during drying, the cellulose fibers are thermally degraded and the strength may be reduced. On the other hand, if the average fiber diameter of the microfiber cellulose is higher than (exceeds) 19 μm, there is no change compared to the pulp, and the reinforcing effect of the resin may become insufficient.
[0133] The method for measuring the average fiber diameter of fine fibers (microfiber cellulose and cellulose nanofibers) is as follows.
[0134] First, 100 ml of an aqueous dispersion of fine fibers having a solid content concentration of 0.01 to 0.1% by mass is filtered with a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of tert-butanol. Then, freeze-drying is performed, and osmium coating is performed to prepare a sample. For this sample, observation based on an electron microscope SEM image is performed at any magnification of 3,000 to 30,000 times according to the width of the fibers constituting it. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersection of the diagonal lines are drawn arbitrarily. Then, the width of a total of 100 fibers intersecting with the three straight lines is visually measured. In addition, the median diameter of the measured value is taken as the average fiber diameter.
[0135] The urethane cellulose fibers P3 or their pulverized products may be subjected to a pretreatment, a bleaching treatment, etc. by a chemical method before fiber opening.
[0136] As pretreatment using chemical methods, for example, hydrolysis of polysaccharides using acid (acid treatment), hydrolysis of polysaccharides using enzymes (enzyme treatment), swelling of polysaccharides using alkali (alkali treatment), oxidation of polysaccharides using oxidants (oxidation treatment), reduction of polysaccharides using reducing agents (reduction treatment), etc. can be exemplified. Among them, as pretreatment using chemical methods, enzyme treatment is preferably performed, and one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment are more preferably performed. Enzyme treatment is described in detail below.
[0137] As the enzyme used in the enzyme treatment, at least any one of a cellulase enzyme and a hemicellulase enzyme is preferably used, and the two are more preferably used together. If these enzymes are used, the fiber opening of the cellulose fiber becomes easier. It should be noted that the cellulase enzyme causes the decomposition of cellulose in the presence of water. In addition, the hemicellulase enzyme causes the decomposition of hemicellulose in the presence of water.
[0138] As cellulase enzymes, for example, enzymes produced by Trichoderma (filamentous fungi), Acremonium (filamentous fungi), Aspergillus (filamentous fungi), Phanerochaete (basidiomycete), Trametes (basidiomycete), Humicola (filamentous fungi), Bacillus (bacteria), Schizophyllum (basidiomycete), Streptomyces (bacteria), Pseudomonas (bacteria), etc. can be used. These cellulase enzymes can be purchased as reagents or commercial products. Examples of commercially available products include Cellulosin T2 (manufactured by HBI), Meicelase (manufactured by Meiji Seika Co., Ltd.), Novozyme 188 (manufactured by Novozyme), Multifect CX10L (manufactured by Genencor), and cellulase enzyme GC220 (manufactured by Genencor).
[0139] In addition, as a cellulase enzyme, any one of EG (endoglucanase) and CBH (cellobiohydrolase) can also be used. EG and CBH can be used alone or in combination. In addition, they can also be used in combination with a hemicellulase enzyme.
[0140] As the hemicellulase enzyme, for example, xylanase, which is an enzyme that decomposes xylan, mannase, which is an enzyme that decomposes mannan, arabanase, which is an enzyme that decomposes arabinan, etc. can be used. In addition, pectinase, which is an enzyme that decomposes pectin, can also be used.
[0141] Hemicellulose is a polysaccharide other than pectin that is located between the cellulose microfibrils of the plant cell wall. There are many types of hemicellulose, and they also differ depending on the type of wood and the interlaminar space of the cell wall. In the secondary wall of coniferous trees, glucomannan is the main component; in the secondary wall of broad-leaved trees, 4-O-methyl glucuronoxylan is the main component. Therefore, in the case of obtaining fine fibers from coniferous bleached kraft pulp (NBKP), it is preferred to use mannanase. In addition, in the case of obtaining fine fibers from broad-leaved bleached kraft pulp (LBKP), it is preferred to use xylanase.
[0142] The amount of enzyme added relative to cellulose fiber is determined, for example, according to the type of enzyme, the type of raw wood (conifer or broadleaf tree), the type of mechanical pulp, etc. Among them, the amount of enzyme added relative to cellulose fiber is preferably 0.1 to 3% by mass, more preferably 0.3 to 2.5% by mass, and particularly preferably 0.5 to 2% by mass. If the amount of enzyme added is less than 0.1% by mass, it is possible that the effect of the addition of the enzyme cannot be fully obtained. On the other hand, if the amount of enzyme added is higher than 3% by mass, cellulose is saccharified, and the yield of fine fibers is likely to decrease. In addition, there is also a problem that the effect improvement consistent with the increment of the addition cannot be confirmed.
[0143] When a cellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weakly acidic region (pH = 3.0 to 6.9) from the aspect of the reactivity of the enzyme reaction. On the other hand, when a hemicellulase enzyme is used as the enzyme, the pH during the enzyme treatment is preferably in the weakly alkaline region (pH = 7.1 to 10.0).
[0144] The temperature during the enzyme treatment is preferably 30 to 70° C., more preferably 35 to 65° C., and particularly preferably 40 to 60° C., when any of a cellulase enzyme and a hemicellulase enzyme is used as the enzyme. If the temperature during the enzyme treatment is 30° C. or higher, the enzyme activity is not easily reduced, and the treatment time can be prevented from being prolonged. On the other hand, when the temperature during the enzyme treatment is 70° C. or lower, the inactivation of the enzyme can be prevented.
[0145] The time of the enzyme treatment is determined by, for example, the type of enzyme, the temperature of the enzyme treatment, the pH during the enzyme treatment, etc. Among them, the general enzyme treatment time is 0.5 to 24 hours.
[0146] After the enzyme treatment, the enzyme is preferably inactivated. Examples of methods for inactivating the enzyme include a method of adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher), and a method of adding hot water at 80 to 100°C.
[0147] Next, the method of the alkali treatment will be described.
[0148] When alkali treatment is performed before fibrillation, the hydroxyl groups of hemicellulose and cellulose contained in the cellulose fibers are partially dissociated and the molecules are anionized, thereby weakening the intramolecular and intermolecular hydrogen bonds, thereby promoting the dispersion of the cellulose fibers during fibrillation.
[0149] As the alkali used in the alkali treatment, for example, organic bases such as sodium hydroxide, lithium hydroxide, potassium hydroxide, aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide can be used. Among them, sodium hydroxide is preferably used from the viewpoint of production cost.
[0150] When enzyme treatment, acid treatment, or oxidation treatment is performed before fiber opening, the water retention of fine fibers can be reduced, the crystallinity can be increased, and the homogeneity can be improved. In this regard, if the water retention of microfiber cellulose is low, it is easy to dehydrate, and the dehydration property of cellulose fiber slurry is improved.
[0151] When cellulose fibers are treated with enzymes, acids, or oxidation treatments, the amorphous regions of hemicellulose or cellulose in pulp are decomposed. As a result, the energy required for fiber opening can be reduced, and the uniformity and dispersibility of cellulose fibers can be improved. However, pretreatment reduces the aspect ratio of microfiber cellulose, so when used as a resin reinforcement material, it is preferable to avoid excessive pretreatment.
[0152] On the other hand, as bleaching treatment, peroxide bleaching, hypochlorite bleaching, chlorine dioxide bleaching, persulfate bleaching, Oxone (potassium monopersulfate complex salt) bleaching, multi-stage bleaching treatment combining these, and reduction bleaching using dithionite, sodium borohydride, etc. can be performed.
[0153] The fiber opening of cellulose fibers can be performed by beating the raw material pulp using a homogenizer such as a refiner, a high-pressure homogenizer, an opposing collision type homogenizer, a high-pressure homogenization device, a mortar friction machine such as a grinder or a mill, a single-screw kneading machine, a multi-screw kneading machine, a kneading refiner, a jet mill, etc. Among them, it is preferably performed using a refiner or a jet mill.
[0154] The average fiber length of microfiber cellulose (average value of the length of single fibers) is preferably 0.02 to 2.0 mm, more preferably 0.05 to 1.5 mm, and particularly preferably 0.1 to 1.0 mm. If the average fiber length is less than 0.02 mm, a three-dimensional network of fibers cannot be formed, and the reinforcing effect of the resin may be reduced. On the other hand, if the average fiber length is more than 2.0 mm, the length is no different from that of the raw material pulp, so the reinforcing effect may be insufficient.
[0155] The average fiber length of the microfiber cellulose can be arbitrarily adjusted by, for example, selecting, pretreating, and fibrillating the raw material pulp P1.
[0156] The ratio of microfiber cellulose having a fiber length of 0.2 mm or less (fineness ratio A) is preferably 25% or more, more preferably 26 to 80%, and particularly preferably 27 to 65%. If the fineness ratio A is less than 25%, the reinforcing effect of the resin may not be sufficiently obtained. On the other hand, if it is more than 80%, the flexural modulus may become insufficient.
[0157] The aspect ratio of the microfibril cellulose is preferably 2 to 15,000, more preferably 10 to 10,000. If the aspect ratio is less than 2, a three-dimensional network cannot be constructed, and thus the reinforcing effect may be insufficient. On the other hand, if the aspect ratio is greater than 15,000, the microfibril cellulose becomes more entangled with each other, and dispersion in the resin may be insufficient.
[0158] The aspect ratio is the value obtained by dividing the average fiber length by the average fiber width. It is known that the larger the aspect ratio, the more sites where hooks are generated, and thus the greater the reinforcing effect, but on the other hand, the ductility of the resin decreases in proportion to the increase in hooks.
[0159] Among the above average fiber length, fineness A and aspect ratio, the fiber length can be measured by using a fiber analyzer "FS5" manufactured by Valmet.
[0160] The fibrillation rate of microfiber cellulose is preferably less than 1.0%, more preferably 0.45% to 0.95%, and particularly preferably 0.60% to 0.90%. If the fibrillation rate exceeds 1.0%, the fibers will agglomerate with each other during drying, and the dispersion in the resin may be insufficient. In this regard, it has been considered that the fibrillation rate is preferably greater than 1.0%. When the fiber length is short and the fibrillation rate exceeds 1.0%, the fibers build a three-dimensional network in the resin, and the reinforcement effect is improved. However, when using fibers with a high fibrillation rate, the fibers are easy to agglomerate, and it is difficult to disperse the fibers in the resin, and the manufacturing conditions are limited (for example, in order to avoid the agglomeration of the fibers, drying takes time), so it is known that it is difficult to mass produce. On the other hand, by using microfiber cellulose with a fibrillation rate of less than 1.0%, the fibers are dispersed even in the case of mass production. In addition, as long as the fineness A is controlled, there is no problem in the three-dimensional network construction, and a high-strength composite resin can be obtained.
[0161] The fibrillation ratio is the ratio of the projected portion of the small fibers to the projected portion of the entire fiber, which is the ratio of the raised portion to the entire fiber including the raised fibers. This value can be measured, for example, using a fiber analyzer "FS5" manufactured by Valmet.
[0162] The crystallinity of microfiber cellulose is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 50%, although the miscibility with pulp and cellulose nanofibers is improved, the strength of the fiber itself is reduced, and thus the strength of the resin may not be improved. On the other hand, the crystallinity of microfiber cellulose is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. If the crystallinity is higher than 95%, the proportion of strong hydrogen bonds in the molecule increases, the fiber itself becomes rigid, and the dispersibility deteriorates.
[0163] The crystallinity of microfibril cellulose can be arbitrarily adjusted by, for example, selecting, pre-treating, and refining the raw pulp P1.
[0164] The crystallinity is a value measured in accordance with JIS K 0131 (1996).
[0165] The viscosity of the microfibril cellulose is preferably 2 cps or more, more preferably 4 cps or more. If the pulp viscosity of the microfibril cellulose is lower than 2 cps, it may be difficult to suppress the aggregation of the microfibril cellulose.
[0166] The viscosity of microfiber cellulose is a value measured in accordance with TAPPI T230.
[0167] The freeness of microfibril cellulose is preferably 500 ml or less, more preferably 300 ml or less, and particularly preferably 100 ml or less. If the freeness of microfibril cellulose exceeds 500 ml, the average fiber diameter of microfibril cellulose exceeds 10 μm, and the strength improvement effect of the resin may not be sufficiently obtained.
[0168] The freeness is a value measured in accordance with JIS P8121-2 (2012).
[0169] The zeta potential of the microfibril cellulose is preferably -150 to 20 mV, more preferably -100 to 0 mV, and particularly preferably -80 to -10 mV. If the zeta potential is lower than -150 mV, the compatibility with the resin is significantly reduced, and the reinforcing effect may become insufficient. On the other hand, if the zeta potential is higher than 20 mV, the dispersion stability may be reduced.
[0170] Next, cellulose nanofibers will be described.
[0171] In this embodiment, the cellulose nanofibers are fine fibers like the microfiber cellulose, and have a unique effect on improving the strength of the resin.
[0172] First, cellulose nanofibers can be obtained by fibrillating (refining) urethanized cellulose fibers P3. As the raw material pulp P1, the same raw material pulp as microfiber cellulose can be used, and preferably the same raw material pulp as microfiber cellulose is used.
[0173] The raw material fibers of cellulose nanofibers can be pretreated and opened in the same manner as in the case of microfiber cellulose. However, the degree of opening is different, for example, it is necessary to open the fibers in such a way that the average fiber diameter is less than 0.1 μm. The following description will focus on the differences from the case of microfiber cellulose.
[0174] The average fiber diameter (average fiber width; average value of the diameter of a single fiber) of the cellulose nanofiber is preferably 4 to 100 nm, more preferably 10 to 80 nm. If the average fiber diameter of the cellulose nanofiber is less than 4 nm, the dehydration property may be deteriorated. In addition, in the method of mixing the cellulose nanofiber with the dispersant, the dispersant cannot fully cover (cannot fully entangle) the cellulose nanofiber, and the dispersibility may not be fully improved. On the other hand, if the average fiber diameter of the cellulose nanofiber is higher than 100 nm, it can no longer be called a cellulose nanofiber.
[0175] The average fiber diameter of the cellulose nanofibers can be adjusted by, for example, selecting the raw material pulp P1, pretreating it, opening it, and the like.
[0176] It should be noted that, unless otherwise specified, the methods for measuring the physical properties of cellulose nanofibers are the same as those for microfiber cellulose.
[0177] The average fiber length (single fiber length) of the cellulose nanofibers is preferably 0.1 to 1,000 μm, more preferably 0.5 to 500 μm. If the average fiber length of the cellulose nanofibers is less than 0.1 μm, a three-dimensional network of cellulose nanofibers cannot be constructed, and the reinforcing effect may be insufficient. On the other hand, if the average fiber length of the cellulose nanofibers is greater than 1,000 μm, the fibers are easily entangled with each other, and the dispersibility may not be sufficiently improved.
[0178] The average fiber length of the cellulose nanofibers can be adjusted by, for example, selecting, pretreating, and fibrillating the raw pulp P1.
[0179] The crystallinity of the cellulose nanofibers is preferably 95 to 50%, more preferably 90 to 60%. When the crystallinity of the cellulose nanofibers is within the above range, the strength of the resin can be reliably improved.
[0180] The crystallinity can be arbitrarily adjusted by, for example, selecting, pretreating, and fiberizing the raw pulp P1.
[0181] The pulp viscosity of the cellulose nanofibers is preferably 1.0 cps or more, more preferably 2.0 cps or more. The pulp viscosity is the viscosity of the solution after dissolving cellulose in a copper ethylenediamine solution. The greater the pulp viscosity, the greater the degree of polymerization of the cellulose. When the pulp viscosity is 1.0 cps or more, dehydration properties can be imparted to the slurry, and the decomposition of the cellulose nanofibers can be suppressed when kneading with the resin, and a sufficient reinforcing effect can be obtained.
[0182] The cellulose nanofibers obtained by fiber opening can be pre-dispersed in an aqueous medium to prepare a dispersion liquid before mixing with other cellulose fibers as needed. The aqueous medium is particularly preferably all water (aqueous dispersion liquid). However, the aqueous medium can also be partly other liquids that are compatible with water. As other liquids, for example, lower alcohols with a carbon number of 3 or less can be used.
[0183] The B-type viscosity of the cellulose nanofiber dispersion (concentration 1%) is preferably 10 to 2,000 cp, more preferably 30 to 1,500 cp. If the B-type viscosity of the dispersion is within the above range, mixing with other cellulose fibers becomes easy and the dehydration property of the cellulose fiber slurry is improved.
[0184] The B-type viscosity (solid content concentration 1%) of the dispersion is a value measured in accordance with "Methods for measuring viscosity of liquids" of JIS-Z8803 (2011). The B-type viscosity is the resistance torque when the dispersion is stirred, and a higher value means more energy is required for stirring.
[0185] The urethane-modified microfibers are dispersed in an aqueous medium as required to prepare a dispersion (slurry). The aqueous medium is preferably entirely water, but an aqueous medium in which a portion is other liquids compatible with water may also be used. As other liquids, lower alcohols having a carbon number of 3 or less may be used.
[0186] The solid content concentration of the slurry is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass. If the solid content concentration is less than 0.1% by mass, excessive energy may be required for dehydration and drying. On the other hand, if the solid content concentration is higher than 10.0% by mass, the fluidity of the slurry itself decreases, and the dispersant may not be uniformly mixed.
[0187] (Acid modified resin)
[0188] The urethanized fine fibers obtained as described above are preferably mixed with an acid-modified resin. The acid groups of the acid-modified resin are ionically or covalently bonded to a part or all of the urethanate groups. The reinforcing effect of the resin is enhanced by the ionically or covalently bonded.
[0189] As the acid-modified resin, for example, an acid-modified polyolefin resin, an acid-modified epoxy resin, an acid-modified styrene-based elastomer resin, etc. can be used. Among them, an acid-modified polyolefin resin is preferably used. The acid-modified polyolefin resin is a copolymer of an unsaturated carboxylic acid component and a polyolefin component.
[0190] As the polyolefin component, one or more kinds of olefin polymers such as ethylene, propylene, butadiene, and isoprene may be selected and used. Among them, polypropylene resins which are propylene polymers are preferably used.
[0191] As the unsaturated carboxylic acid component, for example, one or more kinds can be selected from maleic anhydride, phthalic anhydride, itaconic anhydride, citraconic anhydride, citric anhydride, etc. Among them, maleic anhydride is preferably used appropriately. That is, maleic anhydride-modified polypropylene resin is preferably used.
[0192] The amount of the acid-modified resin mixed is preferably 0.1 to 1000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass relative to 100 parts by mass of the microfiber cellulose. In particular, when the acid-modified resin is a maleic anhydride-modified polypropylene resin, it is preferably 1 to 200 parts by mass, and more preferably 10 to 100 parts by mass. If the amount of the acid-modified resin mixed is less than 0.1 parts by mass, the improvement in strength is insufficient. On the other hand, if the amount is more than 1000 parts by mass, it becomes excessive and the strength tends to decrease.
[0193] The weight average molecular weight of the maleic anhydride-modified polypropylene is, for example, 1,000 to 100,000, or preferably 3,000 to 50,000.
[0194] The acid value of the maleic anhydride-modified polypropylene is preferably from 0.5 mgKOH / g to 100 mgKOH / g, and more preferably from 1 mgKOH / g to 50 mgKOH / g.
[0195] (Dispersant)
[0196] It is more preferable that fibrous cellulose including microfibril cellulose and the like is mixed with a dispersant. As the dispersant, a compound having an amine group and / or a hydroxyl group among aromatic compounds and a compound having an amine group and / or a hydroxyl group among aliphatic compounds are preferred.
[0197] Examples of aromatic compounds having an amino group and / or a hydroxyl group include anilines, toluidines, trimethylanilines, anisidines, tyramines, histamines, tryptamines, phenols, butylated hydroxytoluenes, bisphenol A, cresols, eugenols, gallic acids, guaiacols, picric acids, phenolphthalein, serotonins, dopamines, adrenaline, noradrenaline, thymols, tyrosines, salicylic acids, and the like. Class, methyl salicylate, anise alcohol, salicyl alcohol, mustard alcohol, diphenyl piperidine butanol, diphenyl carbinol, cinnamic alcohol, scopolamine, tryptophan, vanillyl alcohol, 3-phenyl-1-propanol, phenylethyl alcohol, phenoxyethanol, resveratrol, benzyl alcohol, benzoin, mandelic acid, mandelonitrile, benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, mellitic acid, cinnamic acid, etc.
[0198] Examples of aliphatic compounds having an amino group and / or a hydroxyl group include octanols, 2-ethylhexanols, nonanols, decanols, undecanols, lauryl alcohols, tridecanols, myristyl alcohols, pentadecyl alcohols, cetyl alcohols, stearyl alcohols, elaidic alcohols, oleyl alcohols, linoleyl alcohols, methylamines, dimethylamines, trimethylamines, ethylamines, diethylamines, ethylenediamines, triethanolamines, N,N-diisopropyl ethylamines, Amines, tetramethylethylenediamine, 1,6-hexanediamine, spermidine, spermine, adamantane, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, sorbic acid, etc.
[0199] The above dispersants hinder the hydrogen bonding between microfiber cellulose. Therefore, when the microfiber cellulose and the resin are kneaded, the microfiber cellulose is reliably dispersed (redispersed) in the resin. In addition, the above dispersants also have the effect of improving the compatibility of the microfiber cellulose and the resin. From this aspect, the dispersibility of the microfiber cellulose in the resin is improved.
[0200] It should be noted that when mixing the fibrous cellulose and the resin, it is also possible to consider adding a compatibilizer (agent) separately. However, compared to adding the agent at this stage, when the fibrous cellulose and the dispersant (agent) are mixed in advance, the agent is more evenly entangled with the fibrous cellulose, and the effect of improving the compatibility with the resin is enhanced.
[0201] In addition, for example, the melting point of polypropylene is 160°C, so the kneading of fibrous cellulose and resin is carried out at about 180°C. However, when the dispersant (liquid) is added in this state, it will dry instantly. Therefore, there is a method of using a resin with a low melting point to make a masterbatch (a composite resin with a high concentration of microfiber cellulose), and then using a common resin to reduce the concentration. However, resins with low melting points generally have low strength. Therefore, when using this method, the strength of the composite resin may be reduced.
[0202] The amount of the dispersant mixed is preferably 0.1 to 1000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass relative to 100 parts by mass of the microfiber cellulose. If the amount of the dispersant mixed is less than 0.1 parts by mass, the improvement in strength may be insufficient. On the other hand, if the amount of the dispersant mixed is more than 1000 parts by mass, it becomes excessive and the strength tends to decrease.
[0203] In this regard, the acid-modified resin is used to improve compatibility and thus enhance the reinforcing effect by ionically bonding or covalently bonding the acid group with the carbamate group of the microfiber cellulose. Since the molecular weight is large, it is believed that it is also easily compatible with the resin and helps to improve the strength. On the other hand, the dispersant is interposed between the hydroxyl groups of the microfiber cellulose to prevent aggregation, thereby improving the dispersibility in the resin, and since the molecular weight is smaller than that of the acid-modified resin, it can enter the narrow space between the microfiber cellulose that the acid-modified resin cannot enter, and play a role in improving dispersibility and thus improving strength. From the above aspects, it is appropriate that the molecular weight of the acid-modified resin is 2 to 2000 times, preferably 5 to 1000 times the molecular weight of the dispersant.
[0204] To explain this in more detail, the resin powder described later improves the dispersibility of microfiber cellulose by physically interposing between the microfiber cellulose to hinder hydrogen bonding. In contrast, the acid-modified resin improves compatibility by ionically bonding or covalently bonding the acid group with the carbamate group of the microfiber cellulose, thereby improving the reinforcing effect. In this regard, it is the same as the dispersant in hindering the hydrogen bonding between the microfiber celluloses, but the resin powder is micron-sized, so it physically intervenes therebetween to inhibit hydrogen bonding. Therefore, although the dispersibility is lower than that of the dispersant, the resin powder itself melts to form a matrix, so it does not cause a decrease in physical properties. On the other hand, the dispersant is at the molecular level and is extremely small, so it hinders hydrogen bonding in a way that covers the microfiber cellulose, and the effect of improving the dispersibility of the microfiber cellulose is high. However, it remains in the resin and may have the effect of reducing physical properties.
[0205] (Mixing, etc.)
[0206] The mixture of fibrous cellulose, acid-modified resin, dispersant, etc. can be dried and pulverized to form a powder before being kneaded with the resin. According to this embodiment, it is not necessary to dry the fibrous cellulose when kneading with the resin, and the thermal efficiency is good. In addition, especially when a dispersant is mixed in the mixture, even if the mixture is dried, the possibility that fine fibers such as microfibril cellulose cannot be redispersed is extremely low.
[0207] The mixture is dehydrated before drying as required to prepare a dehydrated product. The dehydration can be carried out by selecting one or more dehydrating devices such as a belt press, a screw press, a filter press, a double roll machine, a double mesh former, a valveless filter, a center disc filter, a membrane treatment, a centrifuge, etc. to use.
[0208] The mixture can be dried by selecting one or more of rotary kiln drying, disc drying, airflow drying, medium flow drying, spray drying, drum drying, screw conveyor drying, paddle drying, single-screw kneading drying, multi-screw kneading drying, vacuum drying, stirring drying, etc.
[0209] The dried mixture (dried product) is pulverized to form a powder. The pulverization of the dried product can be carried out by using one or more selected from a bead mill, a kneader, a disperser, a twist mill, a cutting mill, a hammer mill, and the like.
[0210] The average particle size of the powder is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size of the powder exceeds 10,000 μm, the mixing property with the resin may be deteriorated. On the other hand, in order to make the average particle size of the powder less than 1 μm, a large amount of energy is required, which is not economical.
[0211] The average particle size of the powder can be controlled by controlling the degree of pulverization or by classification using a classifying device such as a filter or a cyclone separator.
[0212] The bulk specific gravity of the mixture (powder) is preferably 0.03 to 1.0, more preferably 0.04 to 0.9, and particularly preferably 0.05 to 0.8. A bulk specific gravity exceeding 1.0 means that the hydrogen bonds between the fibrous cellulose are stronger and it is not easy to disperse in the resin. On the other hand, a bulk specific gravity below 0.03 is disadvantageous in terms of transportation cost.
[0213] The bulk specific gravity is a value measured in accordance with JIS K7365.
[0214] The water content of the mixture (powder) is preferably 50% or less, more preferably 30% or less, and particularly preferably 10% or less. If the water content is higher than 50%, the energy required for kneading with the resin is enormous, which is uneconomical.
[0215] The moisture content is a value calculated by the following formula by keeping the sample at 105° C. for 6 hours or more in a constant temperature dryer and defining the mass at the point in time when the mass change is no longer observed as the mass after drying.
[0216] Fiber moisture content (%) = [(mass before drying - mass after drying) ÷ mass before drying] × 100
[0217] The dehydrated / dried microfibril cellulose may contain a resin. If the resin is contained, hydrogen bonding between the dehydrated / dried microfibril cellulose can be inhibited, and dispersibility in the resin during kneading can be improved.
[0218] Examples of the form of the resin contained in the dehydrated and dried microfibril cellulose include powder, granule, and flake forms, among which a powder form (powdered resin; it should be noted that this corresponds to the above-mentioned resin powder) is preferred.
[0219] In the case of powdered form, the average particle size of the resin powder contained in the dehydrated / dried microfiber cellulose is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size exceeds 10,000 μm, it may not be able to enter the kneading device due to the large particle size. On the other hand, if the average particle size is less than 1 μm, it may not be able to hinder the hydrogen bonding between the microfiber cellulose due to its fineness. It should be noted that the resin such as the powdered resin used here and the resin kneaded with the microfiber cellulose (resin as the main raw material) may be the same or different, preferably the same.
[0220] The resin powder having an average particle size of 1 to 10000 μm is preferably mixed in an aqueous dispersion state before dehydration / drying. By mixing in an aqueous dispersion state, the resin powder can be uniformly dispersed between the microfiber celluloses, and the microfiber cellulose can be uniformly dispersed in the composite resin after kneading, which can further improve the strength properties.
[0221] The powdery substance (resin reinforcement material) obtained as above is kneaded with the resin to obtain a fibrous cellulose composite resin. In addition to the method of mixing the granular resin with the powdery substance, the kneading can also be performed by first melting the resin and then adding the powdery substance to the melt. It should be noted that the acid-modified resin, dispersant, etc. can also be added at this stage.
[0222] The kneading process can be, for example, selected from a single screw or a multi-screw kneading machine with more than a twin screw, a mixing roll, a kneader, a roll mill, a Banbury mixer, a screw press, a disperser, etc., or two or more. Among these, a multi-screw kneading machine with more than a twin screw is preferably used. It is also possible to use a multi-screw kneading machine with more than two twin screws in parallel or in series.
[0223] The peripheral speed of the screw of the twin-screw or more multi-screw kneading machine is preferably 0.2 to 200 m / min, more preferably 0.5 to 150 m / min, and particularly preferably 1 to 100 m / min. When the peripheral speed is less than 0.2 m / min, the microfiber cellulose may not be smoothly dispersed in the resin. On the other hand, when the peripheral speed exceeds 200 m / min, the shear force on the microfiber cellulose is too high, and the reinforcing effect may not be obtained.
[0224] The ratio of the screw diameter to the length of the kneading section of the kneading machine used in this embodiment is preferably 15 to 60. When the ratio is less than 15, the kneading section is short and the microfiber cellulose and the resin may not be mixed. On the other hand, when the ratio exceeds 60, the kneading section is too long, so the shear load on the microfiber cellulose increases, and the reinforcing effect may not be obtained.
[0225] The temperature of the kneading treatment is not less than the glass transition temperature of the resin, and varies depending on the type of the resin, but is preferably 80 to 280°C, more preferably 90 to 260°C, and particularly preferably 100 to 240°C.
[0226] As the resin, at least either a thermoplastic resin or a thermosetting resin can be used.
[0227] As the thermoplastic resin, for example, one or more kinds can be selected from polyolefins such as polypropylene (PP) and polyethylene (PE), polyester resins such as aliphatic polyester resins and aromatic polyester resins, polystyrene, polyacrylic resins such as methacrylate and acrylate, polyamide resins, polycarbonate resins, polyacetal resins, etc.
[0228] Among them, at least one of polyolefin and polyester resin is preferably used. In addition, as polyolefin, polypropylene is preferably used. In addition, as polyester resin, as aliphatic polyester resin, for example, polylactic acid, polycaprolactone, etc. can be exemplified, as aromatic polyester resin, for example, polyethylene terephthalate, etc. can be exemplified, but it is preferable to use a biodegradable polyester resin (also referred to as "biodegradable resin").
[0229] As the biodegradable resin, one or more kinds selected from, for example, hydroxycarboxylic acid-based aliphatic polyesters, caprolactone-based aliphatic polyesters, dibasic acid polyesters, and the like can be used.
[0230] As the hydroxycarboxylic acid-based aliphatic polyester, one or more kinds can be selected from homopolymers of hydroxycarboxylic acids such as lactic acid, malic acid, gluconic acid, and 3-hydroxybutyric acid, copolymers using at least one of these hydroxycarboxylic acids, etc. Among them, polylactic acid, copolymers of lactic acid and the above hydroxycarboxylic acids other than lactic acid, polycaprolactone, and copolymers of at least one of the above hydroxycarboxylic acids and caprolactone are preferably used, and polylactic acid is particularly preferably used.
[0231] As the lactic acid, for example, L-lactic acid, D-lactic acid, etc. can be used. These lactic acids may be used alone or in combination of two or more.
[0232] As the caprolactone-based aliphatic polyester, one or more kinds can be selected from, for example, homopolymers of polycaprolactone, copolymers of polycaprolactone and the above-mentioned hydroxycarboxylic acids, and the like.
[0233] As the dibasic acid polyester, one or more kinds selected from, for example, polybutylene succinate, polyethylene succinate, polybutylene adipate, and the like can be used.
[0234] The biodegradable resin may be used alone or in combination of two or more.
[0235] As the thermosetting resin, for example, phenolic resin, urea resin, melamine resin, furan resin, unsaturated polyester, diallyl phthalate resin, vinyl ester resin, epoxy resin, urethane resin, silicone resin, thermosetting polyimide resin, etc. can be used. These resins can be used alone or in combination of two or more.
[0236] The resin may preferably contain an inorganic filler in a ratio that does not hinder heat recovery.
[0237] Examples of the inorganic filler include simple substances, oxides, hydroxides, carbonates, sulfates, silicates, sulfites of metal elements in Groups I to VIII of the periodic table, such as Fe, Na, K, Cu, Mg, Ca, Zn, Ba, Al, Ti, and silicon, and various clay minerals containing these compounds.
[0238] Specifically, for example, barium sulfate, calcium sulfate, magnesium sulfate, sodium sulfate, calcium sulfite, zinc oxide, silicon dioxide, heavy calcium carbonate, light calcium carbonate, aluminum borate, aluminum oxide, iron oxide, calcium titanate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, magnesium carbonate, calcium silicate, clay, wollastonite, glass beads, glass powder, silica sand, silica, quartz powder, diatomaceous earth, white carbon black, glass fiber, etc. can be illustrated. These inorganic fillers can contain multiple types. In addition, it can also be an inorganic filler contained in waste paper pulp.
[0239] Regarding the mixing ratio of fibrous cellulose and resin, it is preferred that fibrous cellulose is 1 mass part or more and resin is 99 mass parts or less, more preferably fibrous cellulose is 2 mass parts or more and resin is 98 mass parts or less, and particularly preferably fibrous cellulose is 3 mass parts or more and resin is 97 mass parts or less. In addition, it is preferred that fibrous cellulose is 50 mass parts or less and resin is 50 mass parts or more, more preferably fibrous cellulose is 40 mass parts or less and resin is 60 mass parts or more, and particularly preferably fibrous cellulose is 30 mass parts or less and resin is 70 mass parts or more. In particular, when fibrous cellulose is 10 to 50 mass parts, the strength of the resin composition, especially the strength of the bending strength and tensile modulus, can be significantly improved.
[0240] In addition, the content ratio of the fibrous cellulose and the resin contained in the finally obtained resin composition is usually the same as the above-mentioned mixing ratio of the fibrous cellulose and the resin.
[0241] About the dissolution parameters of microfibril cellulose and resin (cal / cm 3 ) 1 / 2 The difference between the SP values of microfiber cellulose and MFC Value, SP of resin POL When expressed as a value, it can be expressed as the difference in SP values = SP MFC Value - SP POL The difference in SP value is preferably 10 to 0.1, more preferably 8 to 0.5, and particularly preferably 5 to 1. If the difference in SP value exceeds 10, the microfibril cellulose is not dispersed in the resin and the reinforcing effect cannot be obtained. On the other hand, if the difference in SP value is less than 0.1, the microfibril cellulose dissolves in the resin and cannot function as a filler, and the reinforcing effect cannot be obtained. In this regard, the SP value of the resin (solvent) is preferably 10 to 0.1, more preferably 8 to 0.5, and particularly preferably 5 to 1. If the difference in SP value exceeds 10, the microfibril cellulose is not dispersed in the resin and the reinforcing effect cannot be obtained. On the other hand, if the difference in SP value is less than 0.1, the microfibril cellulose is dissolved in the resin and cannot function as a filler, and the reinforcing effect cannot be obtained. POL Value and SP of microfibril cellulose (solute) MFC The smaller the difference between the values, the greater the enhancement effect. 3 ) 1 / 2 (SP value) is a measure of the intermolecular force acting between a solvent and a solute. The closer the SP values of a solvent and a solute are, the greater the solubility.
[0242] (Other compositions)
[0243] In the resin composition, in addition to the above-mentioned fine fibers, pulp, etc., it can also actively contain fibers from plant materials obtained from various plant bodies such as kenaf, jute, Manila hemp, sisal, wild burdock, balsam pear, banana, pineapple, coconut palm, corn, sugarcane, bagasse, coconut, papyrus, reed, stipa, Indian grass, wheat, rice, bamboo, various coniferous trees (such as cedar and cypress), broad-leaved trees and cotton, etc., or it can passively contain the above-mentioned fibers.
[0244] Can select one or more than two kinds to be added in resin combination from for example antistatic agent, flame retardant, antibacterial agent, coloring agent, free radical scavenger, foaming agent etc. in the scope that does not hinder the effect of the present invention.These raw materials can be added in the dispersion liquid of fibrous cellulose, can be added when fibrous cellulose and resin are kneaded, can be added in their kneaded product, also can utilize other methods to add.Wherein, from the aspect of manufacturing efficiency, preferably add when fibrous cellulose and resin are kneaded.
[0245] The resin composition may contain an ethylene-α-olefin copolymer elastomer or a styrene-butadiene block copolymer as a rubber component. Examples of α-olefins include butene, isobutylene, pentene, hexene, methylpentene, octene, decene, and dodecene.
[0246] (Molding Process)
[0247] The kneaded product of fibrous cellulose and resin can be kneaded again as needed and then molded into a desired shape. The size, thickness, shape, etc. of the molded product are not particularly limited, and the product can be, for example, in the form of sheets, granules, powders, fibers, etc.
[0248] The temperature during the molding process is equal to or higher than the glass transition temperature of the resin, and varies depending on the type of the resin, but is, for example, 90 to 260°C, and preferably 100 to 240°C.
[0249] The kneaded product can be formed by, for example, mold molding, injection molding, extrusion molding, hollow molding, foaming molding, etc. In addition, the kneaded product can be spun into fibers and mixed with the above-mentioned plant materials to form a mat shape or a plate shape. The mixed fibers can be, for example, simultaneously deposited by air lay.
[0250] As the apparatus for molding the kneaded product, one or more kinds of apparatuses selected from, for example, an injection molding machine, an injection molding machine, a hollow molding machine, a blow molding machine, a compression molding machine, an extrusion molding machine, a vacuum molding machine, an air pressure molding machine, etc. can be used.
[0251] The above-mentioned molding can be carried out after kneading, or the kneaded material can be temporarily cooled, and after being made into fragments using a crusher, the fragments are put into a molding machine such as an extruder, an injection molding machine, etc. Of course, molding is not a necessary condition of the present invention.
[0252] (other)
[0253] One feature of the present application is that the fibrillation rate is suppressed while the fineness A of the cellulose fibers is increased. The specific method for achieving this feature is not particularly limited, and it can be adjusted, for example, by the conditions for fiber opening, the type of raw material pulp, etc. Among them, it is preferred that the physical properties of the cellulose fibers before fiber opening satisfy the specific above-mentioned conditions (for example, the fineness A, etc. mentioned above), and it is more preferred to manufacture the fiber-opened cellulose fibers according to the method described above. According to this method, the conditions of fineness A and fibrillation rate can be satisfied with almost no changes to the usual fiber opening.
[0254] In addition, in the composite resin of the present embodiment, the content of the urethanized microfiber cellulose is preferably 0.1 to 99% by mass, more preferably 0.5 to 95% by mass, and particularly preferably 1 to 90% by mass. If the content is less than 0.1% by mass, the reinforcing effect of the resin cannot be fully obtained. On the other hand, if the content exceeds 90% by mass, the resin component is small and processing becomes difficult.
[0255] Example
[0256] Next, examples of the present invention will be described.
[0257] First, a sizing agent is added to a pulp slurry containing a plurality of raw material pulps at a predetermined mixing ratio, and then a pulp sheet is manufactured in such a manner as to achieve a predetermined Cobb sizing degree and basis weight. Next, a urea aqueous solution having a solid content concentration of 40% is used in a coating device to coat the pulp in a predetermined ratio of pulp:urea in terms of the mass ratio converted to the solid content, and the urea-coated sheet is dried in a post-dryer to obtain a urea-coated sheet. The obtained urea-coated sheet is reacted at a predetermined temperature and time in a roll-to-roll reaction device to obtain a sheet having carbamate-modified cellulose as a raw material. Thereafter, the carbamate-modified cellulose sheet is diluted with water to a solid content concentration of 5%, and dissociated using a dissociator. The dissociated carbamate-modified cellulose is diluted and stirred with distilled water, and dehydration and washing are repeated several times to adjust the solid content concentration to 3.5% by mass, thereby obtaining washed carbamate-modified cellulose. The washed carbamate-modified cellulose was beaten with a beater until the fineness A (the ratio of fibers less than 0.2 mm in the fiber length distribution measurement using FS5) was 25% or more, thereby obtaining carbamate-modified microfiber cellulose. Maleic anhydride-modified polypropylene was added to the obtained carbamate-modified microfiber cellulose in a ratio of 67:33 of carbamate-modified microfiber cellulose to maleic anhydride-modified polypropylene, and heated using a contact dryer heated to 140° C. to obtain a carbamate-modified microfiber cellulose-containing material. Subsequently, pellets of polypropylene were mixed with the carbamate-modified microfiber cellulose-containing material in a ratio of 10:90 of carbamate-modified microfiber to other components on a mass basis, and kneaded using a twin-screw kneader at 180° C. and 200 rpm to obtain a carbamate-modified microfiber cellulose composite resin having a fiber mixing ratio of 10%. The urethane-modified microfiber cellulose composite resin with a fiber blending ratio of 10% was cut into a cylindrical shape with a diameter of 2 mm and a length of 2 mm using a pelletizer, and injection-molded into a rectangular test piece (length 59 mm, width 9.6 mm, thickness 3.8 mm) at 180°C.
[0258] The bending modulus, bending strength, and inclusion area ratio of each test piece obtained were investigated. The results are shown in Table 1. It should be noted that the method of each test is as follows. In addition, before fiber opening in the table means immediately before the above-mentioned beating (immediately before being made into microfiber cellulose).
[0259] (Inclusion area ratio)
[0260] In the inclusion measurement according to JIS P 8145:2011, the area ratio is less than 10mm 2 / m 2 Recorded as 0, 10mm2 / m 2 The above are marked as ×.
[0261] (Flexural modulus)
[0262] When the base PP (1.48 GPa) is set to 1.00, 1.50 times or more is represented as 0, and less than 1.50 times is represented as ×.
[0263] (Bending Strength)
[0264] When the basic PP (53.4 MPa) is set to 1.00, 1.25 times or more is represented as 0, and less than 1.25 times is represented as ×.
[0265] [Table 1]
[0266]
[0267] Industrial Applicability
[0268] The present invention can be used as a fibrous cellulose composite resin and a method for producing the same.
[0269] Description of Reference Numerals
[0270] 100 Papermaking process
[0271] 110 Network Department
[0272] 120 Pressing Section
[0273] 130 Pre-drying section
[0274] 200 Coating process
[0275] 210 Coating Department
[0276] 220 Post-drying section
[0277] P1 Raw pulp
[0278] P2 Cellulose fiber content
[0279] P3 urethanized cellulose fiber
[0280] P4 urethane microfiber
[0281] X1 Papermaking and coating process
[0282] X2 Urethane Process
[0283] X3 Fiber opening process
Claims
1. A fibrous cellulose composite resin, characterized in that Contains fibrous cellulose and resin, The fibrous cellulose is carbamate-modified microfibril cellulose in which a part or all of the hydroxyl groups are substituted with carbamate groups, the fineness ratio A is 25% or more, and the fibrillation ratio is 1.0% or less.
2. The fibrous cellulose composite resin according to claim 1, wherein The raw material fiber of the fibrous cellulose has a fineness A of 20% or more and a freeness of 300 ml to 700 ml.
3. The fibrous cellulose composite resin according to claim 1, wherein The content of the urethanized microfiber cellulose is 1% by mass to 90% by mass.
4. A fibrous cellulose-containing material, characterized in that: Include: Carbamate-modified microfiber cellulose in which a part or all of the hydroxyl groups are substituted with carbamate groups, the fineness A is 25% or more, and the fibrillation rate is 1.0% or less; and Maleic anhydride modified resin.
5. A method for producing a fibrous cellulose composite resin, characterized in that: Raw pulp is made into paper to form a strip-shaped pulp sheet. At least one of urea and a urea derivative is applied to the pulp sheet and heated to prepare a urethanized pulp sheet. The urethanized pulp sheet is opened to prepare urethanized microfiber cellulose having a fineness A of 25% or more and a fibrillation rate of 1.0% or less. The urethanized microfiber cellulose and a resin are kneaded to prepare a fibrous cellulose composite resin.
Citation Information
Patent Citations
Fine cellulose fiber, manufacturing method therefor, slurry, and composite
JP2019001876A